Sec-CompFY: secure compartment for you - Azmi, Muhammad; Nu’man, Muhammad; Hafifi, Danial; Wee, Hassnah (Universiti Teknologi Mara, Kedah, 2022)
National Transformation 2050's strategic objective is to build an educated and aware society in the future. In addition, the United Nations' 17 Sustainable Development Goals are an urgent call to action for developing and developed countries to work together in a global partnership. In addition to combating climate change and preserving land, the goals emphasise minimising gaps in innovation, security, and the economy. Therefore, the nation’s job to promote specific behaviours, cognitive processes, and attitudes will boost the openness and knowledge of the next generation. Thus, "Sec- CompFy: Secure Compartment For You" will be developed to keep your belongings while spending time in the library safely. Using today's latest technology, precious things will be stored safely and without concern, giving library patrons a novel experience. Sec-CompFY is a security initiative that employs the most recent library-compatible technology and intends to comfort users who are comfortable reading or studying alone in libraries. The primary criteria are product quality, energy efficiency, product planning and design, materials, and resources. A keyless system and a simple design is a novel approach to meeting Sec-CompFY's requirements.